Phylogenetic reconstruction of the genus Pseudaeginella (Amphipoda: Caprellidae), with the description of a new species from Brazil. Issue 2 (17th February 2019) - Iwasa-Arai, Tammy; Siqueira, Silvana Gomes Leite; Machado, Glauco Barreto De Oliveira; Leite, Fosca Pedini Pereira
Abstract : The genus Pseudaeginella is analysed herein by cladistic methods based on a morphological data matrix of 49 characters × 18 terminal taxa. Based on the results, we comment on the phylogenetic position of Paradeutella within Pseudaeginella, and we propose Pseudaeginella multispinosa comb. nov. and Pseudaeginella tanzaniensis comb. nov. Pseudaeginella freirei sp. nov. is described from the Abrolhos Bank, north-eastern Brazil. We provide an updated key to the Pseudaeginella species. http://www.zoobank.org/urn:lsid:zoobank.org:pub:F573E845-822E-41D6-8F58-FE54C5653A53